Perancangan Produk Selai Jeruk Nipis sebagai Upaya Pengembangan Potensi Agroindustri di Desa Bolo, Kecamatan Ujung Pangkah, Kabupaten Gresik. - Yunita Siti Mardhiyyah; Rizky Noviasri; Muhammad Faisal Ibrahim (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
Bolo village is very promising to be developed as a village agro-industry with its lime fruits product. However, the price fluctuations and a decrease in quality during the shelf life of fresh lime have become challenges. This problem was identified by the UISI 2020 Student Community Service group. The goal of this community service is to find alternative solutions for making lime agro-industry based production, which is in the form of post-harvest processing of lime into jam. The implementation steps are (1) analysis of environmental conditions; (2) jam production; (3) calculation of the nutritional value of jam; (4) product packaging and branding; (5) calculation of production costs; (6) socialization of the